Personal intelligence and its relationship to social sympathy Among university students (Journal of the College of Basic Education, 2020)
The current research aims to identify the personal self-intelligence of university students، identify social empathy among university students، and define the nature of the relationship between self-personal intelligence and social empathy among university students.The current research identifies the Mustansiriya University students from the (scientific and human) colleges for the early morning studies of both sexes (male-female). The researcher adopted a measure of self-intelligence for the self-intelligence، and the researcher adopted the trainee and Habitsen scale for social empathy from Al-Rubaie (2001). The researcher found that the students of the university enjoy a level of self-personal intelligence higher than the average، The university has a level of social empathy higher than the average satisfactory، and there is a positive positive relationship between the two variables.